(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2023)
In this work, the Monte Carlo MCNPX (2.7.0) code was used to evaluate the radioprotective properties of ten ornamental granitic samples produced in Brazil. For each sample of granite, the mass attenuation coefficient (µ/ρ) and half-value layer (HVL) were evaluated using the photon energy emitted by the following radioisotopes: 241Am (59,5 keV), 133Ba (356 keV), 137Cs (662 keV), 60Co (1250 keV), and 22Na (1274 keV). The MCNPX results showed agreement with the values obtained by using the XCOM database, as well as with theoretical and experimental results, available on the literature. The computational model built in this work can be used by the scientific community interested in parameters involving new materials for gamma radiation shielding, which has been used in different areas of the nuclear sciences.